HARMFUL EFFECT OF INSECTICIDES AGAINST PREDATOR, COCCINELLA SP. (LADY BIRD BEETLE) ONEGGPLANT (SOLANUMMELONGENA L.) - GHOSH, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
Among the different predators lady bird beetles play an important role in the natural suppression of destructive insect pests viz. jassid, aphid, thrips, mites infesting vegetable crops. Coccinella sp., an important lady bird beetle in the sub-Himalayan region of north-east India was found very active on different insect pests of eggplant (Solanum melongena L.). Its population was recorded higher (4.87 Coccinella/ plant) during March-April (1 1" standard week) when the mean temperature, mean relative humidity and weekly rainfall were 23.8°C, 742% and 8.2 mm, respectively and then declined gradually. Coccinella sp. incidence showed significant positive correlation (p=0.05) with maximum temperature and significant negative correlation with relative humidity whereas with mean temperature and rainfall the correlation was negative but nonsignificant. Insecticides of biological origin were relatively less harmful to Coccinella sp. than synthetic ones. The pathogens, Bacillus thuringiensis and Beauveria bassiana caused significant lower killing of the predator (less than 40%) whereas the synthetic insecticides, DDVP and malathion caused significantly higher killing (more than 50%). Botanical insecticide, neem caused lower killing (less than 40%) of the Coccinella sp. Botanical and microbial insecticides are biopesticides having less or no hazardous effects on bio-agents, human health and environment, and, therefore, they can be incorporated in IPM programmes and organic farming.